Urban-rural disparities in the association between long-term exposure to high altitude and malnutrition among children under 5 years old: evidence from a cross-sectional study in Tibet - Xianzhi Li; Yajie Li; Xiangyi Xing; Yu Liu; Zonglei Zhou; Shunjin Liu; Yunyun Tian; Qucuo Nima; Li Yin; Bin Yu (Cambridge University Press, 2023)
Abstract Objective: To assess urban-rural disparities in the association between long-term exposure to high altitude and malnutrition among children under 5 years old. Design: A three-stage, stratified, cluster sampling was used to randomly select eligible individuals from July to October 2020. The data of participants, including demographic characteristics, altitude of residence, and nutritional status, were collected via questionnaire and physical examination. Setting: Tibet, China. Participants: Children under 5 years old in Tibet. Results: Totally, 1975 children under 5 years old were included in this study. We found that an additional 1000 m increase in altitude was associated with decreased Z-scores of height-for-age (β = -0·23, 95 % CI: -0·38, -0·08), Z-scores of weight-for-age (β = -0·24, 95 % CI: -0·39, -0·10). The OR for stunting and underweight were 2·03 (95 % CI: 1·51 to 2·73) and 2·04 (95 % CI: 1·38 to 3·02) per 1000 m increase in altitude, respectively; and OR increased rapidly at an altitude above 3500 m. The effects of long-term exposure to high altitudes on the prevalence of underweight in rural children were higher than that in urban children (P < 0·05). Conclusions: High-altitude exposure is tightly associated with malnutrition among children under 5 years old. Improving children's nutrition is urgently needed in areas above 3500 m, especially in rural ones.